Cooperative Analysis of a Scorpion-like Composite Robot with Multiple Arms - Xue Jiaolong; Gao Qiang; Zhang Jie; Yan Hongwei (Jixie chuandong, 2022)
Aiming at the low efficiency of temperature measurement in coke oven factory, a type of scorpion-like composite robot is designed to measure temperature in coke ovens. The robot works in combination with the structural characteristics of the scorpion. It uses the scorpion's double pincers to lift the lid of the furnace and measures the temperature in the furnace with the infrared temperature measurement of the scorpion tail. In order to verify the rationality of the robot structure, the overall D-H structure of the composite robot is modeled by Matlab, the forward and inverse kinematics of the legs of the composite robot are analyzed, and the working space probability model of the infrared thermometer with both arms and tail is obtained by Monte Carlo method simulation. In order to verify the motion stability of the robot, the stable gait of the composite robot was obtained through Adams simulation. It lays a solid foundation for further robot research.